The Possible Job Creation and Job Destructive Effects of Technological Development - Boros, József (International Journal of Engineering and Management Sciences, 2020)
Throughout history, technological change has often provided the basis for employee anxiety. Between 1811 and 1816, a group of workers in England who called themselves "Luddists" destroyed machines, because they thought it would endanger their workplace. 19th-century thinkers and economists such as Karl Marx and David Ricardo predicted that mechanizing the economy would ultimately worsen workers' conditions, depriving them of a decent wage. Over the last century, John M. Keynes (1930s) and Wassily Leontief (1950s) have expressed their fears that more and more workers will be replaced by machine solutions that will lead to unemployment. In recent years, Brynjolfsson and McAfee (2014) have argued that existing technologies reduce the demand for labor and put some of the human workforce at a permanent disadvantage. However, there are a number of compensation mechanisms that can offset the initial displacement effects of automation and process innovation in general (Vivarelli, 2015). First of all, while workers are being replaced in industries that introduce new machine technology, additional workers in new industries are needed. Second, automation (and process innovation in general) reduces average costs. Acemoglu and Restrepo (2017) found that this results, on the one hand, in the effect of price productivity (“priceproductivity”) (as production costs decrease, the industry can expand and increase labor demand); and, on the other hand, it leads to economies of scale in production (the reduction in costs due to automation leads to an increase in total output and increases the demand for labor in all industries). Similarly, Vivarelli (2015) argues that lower average costs can result in lower prices (if the industry's market structure is perfectly competitive), stimulate product demand, or result in extra profits (if the industry's structure is not perfectly competitive). If these extra profits are reinvested in the company, this investment can create new jobs. The presentation intends to present these counterbalancing cases and to provide real examples based on the literature.